The immunomodulatory role of IDO1-Kynurenine-NAD+ pathway in switching cold tumor microenvironment in PDAC - Anu, R. I.; Shiu, Kai-Keen; Khan, Khurum Hayat (Frontiers in Oncology, 2023)
Pancreatic ductal adenocarcinoma (PDAC) is the most common exocrine tumor of the pancreas characterized by late diagnosis, adverse overall 5-year survival, a higher propensity for metastatic disease, and lack of efficacy of systemic therapy options. These adverse outcomes can be partly attributed to complex tumor microenvironment (TME). Over the past decade, immunotherapy has revolutionized the management of certain cancers; thus far, the immunologically ‘non-inflamed’ tumor microenvironment in PDACs has proven to be challenging. Indolamine 2,3-dioxygenase 1 (IDO1) is the rate-limiting enzyme in the catabolic pathway of L-Tryptophan, an essential amino acid, that gives rise to the immunosuppressive metabolite Kynurenine. IDO1, Indolamine 2,3-dioxygenase 2 (IDO2), and Tryptophan 2,3-dioxygenase (TDO) are the key enzymes in the tryptophan catabolic pathway but we focus on the role of the predominant enzyme form IDO1 in this review. Nicotinamide phosphoribosyl transferase (iNAMPT) regulates the intracellular concentration of NAD and is upregulated in the tumor. In light of the potential role of IDO1 as a driver of hostile TME in PDAC and NAD+ as a key coenzyme in anti-tumor immune response, this review urges focus on extensive research and initiation of clinical trials using IDO1 and NAMPT inhibitors in pancreatic cancer in the future.